PENGARUH LITERASI KEUANGAN, PERILAKU KEUANGAN DAN PENDAPATAN TERHADAP KEPUTUSAN INVESTASI - Latifah, R. R. Talitha Felicia; Juwita, Himmiyatul Amanah Jiwa (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The purpose of this study is to identify the effects of financial literacy, financial behavior, and income on investment decision. This quantitative explanatory research was conducted on the employees of PT ASABRI (Persero) in branch offices throughout East Java for six months, from April to December 2022. The data was harvested through questionnaires distributed to 51 respondents and was analyzed using multiple linear regression, F test, t test, and coefficient of determination test performed in SPSS version 28. This study finds that financial literacy significantly influences investment decision, that financial behavior significantly affects investment decision, and that income significantly impacts investment decision. These findings explain that income and the knowledge and capability of individuals used to manage their personal finance are key factors for their decision to make investments.